2011
DOI: 10.1103/physrevlett.107.060402
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg Excitations in Bose-Einstein Condensates in Quasi-One-Dimensional Potentials and Optical Lattices

Abstract: We experimentally realize Rydberg excitations in Bose-Einstein condensates of rubidium atoms loaded into quasi-one-dimensional traps and in optical lattices. Our results for condensates expanded to different sizes in the one-dimensional trap agree well with the intuitive picture of a chain of Rydberg excitations. We also find that the Rydberg excitations in the optical lattice do not destroy the phase coherence of the condensate, and our results in that system agree with the picture of localized collective Ryd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
158
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 28 publications
3
158
0
Order By: Relevance
“…Further research has found collective quantum jump between a state of low Rydberg population and a state of high Rydberg population [8]. These researches open up a new window to use Rydberg atoms for quantum nonequilibrium dynamics simulation [9].When two atoms are close, the excitation of one atom is prohibited by an already excited neighboring atom due to the level shift by the strong dipole-dipole interaction at a short distance [10]. This phenomenon is called dipole blockade effect and has played an important role in current Rydberg atom researches [11][12][13].…”
mentioning
confidence: 99%
“…Further research has found collective quantum jump between a state of low Rydberg population and a state of high Rydberg population [8]. These researches open up a new window to use Rydberg atoms for quantum nonequilibrium dynamics simulation [9].When two atoms are close, the excitation of one atom is prohibited by an already excited neighboring atom due to the level shift by the strong dipole-dipole interaction at a short distance [10]. This phenomenon is called dipole blockade effect and has played an important role in current Rydberg atom researches [11][12][13].…”
mentioning
confidence: 99%
“…array of cavities [27,28], atoms within a cavity [29], and Rydberg atoms in an optical lattice [30][31][32][33]. Recently, it was pointed that [34], an imaginary transverse field may be implemented by optically pumping a qubit state into the auxiliary state.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The blockade originates from large electrostatic energy shifts between atoms in Rydberg states and has recently been demonstrated experimentally for atoms trapped in individual optical traps [19,20]. Also first experiments with Rydberg atoms in a lattice [21] have been conducted. We will discuss which anyonic interactions can be realized in such a system and how anyonic degrees of freedom can be measured experimentally.…”
mentioning
confidence: 99%
“…Hamiltonian (1) has been studied in a number of theoretical works [22][23][24][25] and recent experiments have shown that it accurately reflects the physics of laser driven Rydberg gases [21,26]. We are here interested in a parameter regime in which the nearest neighbor interaction is the largest energy scale, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation